Bioinformatic Analysis of Epigenetic and MicroRNA Mediated Regulation of Drought Responsive Genes in Rice - Shaik, Rafi; Ramakrishna, Wusirika (PloS one, 2012)
Drought stress response is a complex trait regulated at multiple levels. Changes in the epigenetic and miRNA regulatory landscape can dramatically alter the outcome of a stress response. However, little is known about the scope and extent of these regulatory factors on drought related cellular processes and functions. To this end, we selected a list of 5468 drought responsive genes (DRGs) of rice identified in multiple microarray studies and mapped the DNA methylation regions found in a genome wide methylcytosine immunoprecipitation and sequencing (mCIP-Seq) study to their genic and promoter regions, identified the chromatin remodeling genes and the genes that are targets of miRNAs. We found statistically significant enrichment of DNA methylation reads and miRNA target sequences in DRGs compared to a random set of genes. About 75% of the DRGs annotated to be involved in chromatin remodeling were downregulated. We found one-third of the DRGs are targeted by two-thirds of all known/predicted miRNAs in rice which include many transcription factors targeted by more than five miRNAs. Clustering analysis of the DRGs with epigenetic and miRNA features revealed, upregulated cluster was enriched in drought tolerance mechanisms while the downregulated cluster was enriched in drought resistance mechanisms evident by their unique gene ontologies (GOs), protein-protein interactions (PPIs), specific transcription factors, protein domains and metabolic pathways. Further, we analyzed the proteome of two weeks old young rice plants treated with a global demethylating agent, 5-azacytidine (5-azaC), subjected to drought stress and identified 56 protein spots that are differentially expressed. Out of the 56 spots, 35 were differently expressed in the sample with both demethylation and drought stress treatments and 28 (50%) were part of DRGs considered in the bioinformatic analysis.